Sammy Gronemann's "Little Mirror": Translating "Tohuwabohu" into "Utter Chaos" - Milbouer, Penny (Naharaim, 2024)
Reflecting on her English translation of Sammy Gronemann's novel Tohuwabohu (originally published in German in 1920), which was released under the title Utter Chaos in 2016, Penny Milbouer's essay reconstructs the enthusiastic reception of the novel by Albert Einstein, a discerning and knowledgeable reader. Milbouer explores the resonance between Gronemann's and Einstein's perspectives on modern German Jewish identity, nationalism, and antisemitism. Her essay examines Einstein's disillusionment with American Jews' assimilationist tendencies and analyses reasons for the failure to recognize Gronemann's satire. Delving into Einstein's experiences with antisemitism in America, Milbouer describes his evolving views on Zionism, contrasting American and European Jewish identities in the "little mirror" of Gronemann's novel. Her conclusion highlights the contemporary relevance of Gronemann's satire and Einstein's warnings about the persistence of antisemitism, confirming that American Jews cannot escape confronting their identity or responding to discrimination and persecution.